The expression
2 4 1 + 2 9 7
can be expressed as b a , where a and b are coprime positive integers. What is a + b ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I didn't know what a and b were supposed to represent, or what a/b had to do with a + b. So I just did the calculation and got 3 1/6.
First, we see that 2 4 1 = 4 9 , so the square root of 2 4 1 is 2 3 . We also see that 2 9 7 = 9 2 5 , so the square root of 2 9 7 is 3 5 . By adding 2 3 and 3 5 , we get 6 1 9 . Adding 19 and 6 yields us 25, so our answer is 2 5
o helo bhai ye divide ho rahy hn add nai
2 4 1 = 4 9 and 2 9 7 = 9 2 5
Take root...
4 9 = 2 3 a n d 9 2 5 = 3 5
So, we have:
2 3 + 3 5
Calculate Least Common Multiple
2 3 + 3 5 = 6 9 + 1 0
6 9 + 1 0 = 6 1 9 = b a
Then... a = 1 9 and b = 6
a + b = 1 9 + 9 = > a + b = 2 5
2 4 1 + 2 9 7
⟹ 4 9 + 9 2 5
⟹ 2 3 + 3 5
⟹ 6 9 + 1 0
⟹ 6 1 9 = b a
So, a = 1 9 and b = 6
And a + b = 1 9 + 6 = 2 5
2 4 1 + 2 9 7 = 4 9 + 9 2 5 = 2 3 + 3 5 = 3 ∗ 2 9 + 1 0 = 6 1 9 = > a = 1 9 , b = 6 = > a + b = 2 5
Express as an improper fraction . We have , sqrt.of 9/4+sqrt. of 25/9
= 3/2+5/3 = 19/6.
a+b = 25
2 4 1 + 2 9 7 4 9 + 9 2 5 4 9 + 9 2 5 2 3 + 3 5 2 × 3 3 × 3 + 3 × 2 5 × 2 6 9 + 6 1 0 6 9 + 1 0 6 1 9 So a = 1 9 a n d b = 6 so a + b = 1 9 + 6 = 2 5
Square root always means positive square root, because we dont multiply with -1 inside the radical sign. So sqrt{9/4} + sqrt{25/9} = 3/2+5/3 = 19/6. So answer is 25
sqrt(2 1/4) + sqrt(2 7/9) sqrt(9/4) + sqrt(25/9) 3/2 + 5/3 25 so ans is 25
convert the mixed fraction into a improper fraction(for both cases)and then find the square root of it (for both) and then add it to get the answer
.
Problem Loading...
Note Loading...
Set Loading...
Simplify this to get- 4 9 + 9 2 5 ⇒ 2 3 + 3 5 ⇒ 6 9 + 1 0 ⇒ 6 1 9
From here, we get a = 1 9 and b = 6 . Hence a + b = 1 9 + 6 = 2 5 .